Local velocity scaling in upward flow to tooth impeller in a fully turbulent region - Šulc R.; Ditl P.; Fořt I.; Jašíková D.; Kotek M.; Kopecký V.; Kysela B. (EDP Sciences, 2019)
The hydrodynamics and flow field were measured in an agitated vessel using 2-D Time Resolved Particle Image Velocimetry (2-D TR PIV). The experiments were carried out in a fully baffled cylindrical flat bottom vessel 400 mm in inner diameter agitated by a tooth impeller 133 mm in diameter. Distilled water was used as the agitated liquid. The velocity fields were investigated in the upward flow to the impeller for three impeller rotation speeds – 300 rpm, 500 rpm and 700 rpm, corresponding to a Reynolds number in the range 94 000 < Re < 221 000. This means that fully-developed turbulent flow was reached. This Re range secures the fully-developed turbulent flow in an agitated liquid. In accordance with the theory of mixing, the dimensionless mean and fluctuation velocities in the measured directions were found to be constant and independent of the impeller Reynolds number. On the basis of the test results the spatial distributions of dimensionless velocities were calculated. The axial turbulence intensity was found to be in the majority in the range from 0.4 to 0.7, which corresponds to the middle level of turbulence intensity.
Keywords: mixing; high shear impeller; velocity field